Update on the pharmacogenetics of the vitamin D receptor and osteoporosis. (March 2009) - Gennari, Luigi; Merlotti, Daniela; De Paola, Vincenzo; Martini, Giuseppe; Nuti, Ranuccio
Vitamin D and calcium are essential for normal skeletal growth and for maintaining the mechanical and structural integrity of the skeleton. Reduced intake of calcium and vitamin D may be associated with reduced bone mass and osteoporosis while a chronic and severe vitamin D deficiency may lead to osteomalacia. Given the importance of vitamin D in bone homeostasis, common polymorphisms in the vitamin D receptor gene were the first to be investigated as possible determinants of bone mass and fracture risk. Even though results are still conflicting and the molecular mechanisms by which these polymorphisms influence receptor activity remain in part to be investigated, an additional important issue is represented by their potential pharmacogenomic and pharmacogenetic implications. This review analyzes major pharmacogenetic studies of polymorphisms in the vitamin D receptor gene and osteoporosis.